THE IMPACT OF SEXUAL VIOLENCE IN THE MEDIA ON MANDAILING NATAL WOMEN - Ahmad Salman Farid; Rengga Irfan (Universitas Islam Negeri Mataram, 2022)
The substance of the news while interpreting the incidents of sexual violence through news content should fulfill the journalistic code of ethics. News of sexual violence in particular, is a news subject that commonly emerges on online media in Mandailing Natal Regency. This research adopts a qualitative method through content analysis of sexual violence news on online media in the Mandailing Natal. The results of this study reveal that the news information released by online media regarding sexual violence has met the norms of journalistic regulations and the journalistic code of ethics. The news also masked the identities of victims of sexual violence. In addition, there were inadequacies in the news material in the form of typos and mixing of facts and opinions. Victims who view news broadcasts of sexual violence are known to have emotional consequences in the form of behavioral and cognitive issues that lead to psychological pressure on victims.